2013
DOI: 10.3109/08037051.2013.838827
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of isolated systolic hypertension in adult populations from the Han, Uygur and Kazakh ethnic groups in Xinjiang, China

Abstract: The prevalence of ISH in Xinjiang is higher than average and exhibits a gender difference. There is a trend of increased prevalence with increasing age. Populations with obesity, diabetes or dyslipidemia, and patients who have hypertension combined with obesity and/or diabetes, should be aware of early preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Possibly as a consequence of differences in lipid profiles, HOMA-IR of Hans was the highest, while Kazaks’ was the lowest, and an inverse relationship was observed for the Matsuda index. Those observations are in line with the prevalence of diabetes mellitus of 8.0%, 6.0%, and 3.5% in Hans, Uygurs, and Kazaks, respectively [ 7 ]. HOMA-IR [ 8 ] and the Matsuda index [ 9 ] are good predictors of diabetes mellitus development even in individuals with normal glucose tolerance [ 10 ], but it is important to highlight that they do not represent exactly the same biological processes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Possibly as a consequence of differences in lipid profiles, HOMA-IR of Hans was the highest, while Kazaks’ was the lowest, and an inverse relationship was observed for the Matsuda index. Those observations are in line with the prevalence of diabetes mellitus of 8.0%, 6.0%, and 3.5% in Hans, Uygurs, and Kazaks, respectively [ 7 ]. HOMA-IR [ 8 ] and the Matsuda index [ 9 ] are good predictors of diabetes mellitus development even in individuals with normal glucose tolerance [ 10 ], but it is important to highlight that they do not represent exactly the same biological processes.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, Kazaks were found to have a lower prevalence of diabetes compared with Uygurs, while Hans had the highest risk of diabetes even after adjustment for body mass index (BMI) or waist circumference (WC). Kazaks were more prone to hypertension than the other two populations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to mention that the epidemiological profile of IDH in the current study is different from what we observed in ISH previously. In our previous study [ 36 ] we found that the prevalence of ISH was 12.4% in the Han, 11.75% in the Uygur and 11.50% in the Kazakh populations, which were higher than the prevalence of IDH in all three ethnicity groups. Moreover, ISH was more common in women than in men in Han participants, but there were no significant gender difference in the Uygur and Kazakh populations.…”
Section: Discussionmentioning
confidence: 75%
“…The Cardiovascular Risk Survey (CRS) is a cross-sectional, observational cohort study designed to investigate the prevalence, incidence, and risk factors for cardiovascular diseases and to determine the genetic and environmental contributions to atherosclerosis, coronary artery disease and cerebral infarction in the Han, Uygur, and Kazakh population in the Xinjiang province of West China and detailed description of study population and methods were described in the previous studies [31,32]. We used a stratified sampling method to select a representative sample of the general population of Han, Uygur and Kazakh Chinese in this region.…”
Section: Study Populationmentioning
confidence: 99%